Nonmalignant mortality among workers in six Norwegian aluminum plants - Romundstad, Pål; Andersen, Aage; Haldorsen, Tor (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study investigated the associations between exposure to fluorides and polycyclic aromatic hydrocarbons (PAH) and mortality from nonmalignant diseases among workers in the Norwegian primary aluminum industry.' ' METHODS ': 'Mortality among 10 857 men, employed for more than 3 years in 1 of 6 aluminum plants, was investigated from 1962 to 1996, giving 239 246 person-years during follow-up. A job-exposure matrix covering all 6 plants was used to estimate the individual exposure to total fluorides and particulate PAH. The observed cause-specific deaths were compared with expected figures calculated from national rates. Dose-response relations were investigated by internal comparisons using Poisson regression and by stratified analyses for standardized mortality ratio. Potential confounding by smoking was investigated in subanalyses restricted to 3 of the plants for which information on smoking habits was accessible.' ' RESULTS ': 'Mortality from circulatory disease was slightly lower than expected [SMR 0.95, 95% confidence interval (95%CI) 0.9-1.0], while there was an increased mortality from asthma, emphysema, and chronic bronchitis combined, SMR 1.2 (95% CI 1.0-1.5). Mortality from these diseases was associated with cumulative exposure to fluorides. The rate ratio in the internal analysis rose steadily to 2.5 (95% CI 1.5-4.3) for the upper exposure category. No association was observed between cumulative fluoride exposure or PAH exposure and circulatory mortality.' ' CONCLUSIONS ': 'The study showed an association between exposure to potroom emissions measured by fluorides and mortality from asthma, emphysema, and chronic bronchitis combined.
Keywords: asthma; chronic obstructive lung disease; circulatory disease; fluoride; polycyclic aromatic hydrocarbon; potroom emission; primary aluminum smelter